Molecular identification of a steroidogenesis-related gene, star3, and its function in gonadal development of Hyriopsis cumingii - Yang Gu; Xiaozhao Shangguan; Yingrui Mao; Weizhong Li; Yijin Ren; Zhengxin Li; Huohong lv; Yihan Wu; Guiling Wang (Aquaculture Reports)
Star3 is located in sex hormone synthesis signaling pathway associated with gonadal development. In this study, star3 was first cloned from the gonad of Hyriopsis cumingii. The cDNA of star3 in H. cumingii was 2072 bp in length, concluding an open reading frame (ORF) of 1419 bp, encoding 472 amino acids with a conserved START structural domain. Tissue distribution analysis showed star3 highest expressed mainly in gonad, which had higher transcription levels in testis than that in ovary. Significant hybridization signals were detected on the follicle wall cell of male gonad. Gonad expression patterns revealed star3 highest expressed at two months old during juvenile stages. After RNA interference with star3, expression levels of cyp17a and 17β-hsd11 was repressed. Furthermore, contents of pregnenolone, testosterone, and estradiol in gonad were reduced significantly. These results suggest star3 may be involved in sex hormone synthesis and play an important role in early gonadal development of H. cumingii.